Proceedings Book of The 10th Annual Scientific Meeting (ASM) of Indonesia Sports Medicine Association (ISMA) in conjunction with the 2nd Malaysian Indonesia Sports Symposium (MISS) - Perhimpunan Dokter Spesialis Kedokteran Olahraga (Physical Therapy Journal of Indonesia, 2025)
Greetings from Chairman of Indonesian Sports Medicine Asssociation As the chairman of Indonesian Sports Medicine Association (ISMA), I am so grateful that we are organising the 2025 Annual Scientific Meeting (ASM) in conjunction with the Malaysian-Indonesian Sports Symposium (MISS) in Bali from October 30 - November 1, 2025. With the theme of “The Winning Team: Integrating Sports Medicine into Primary Care”, ASM are aiming to re-affirm our role in building a healthier nation through our profession, which extend not only to the competitive athlete, but also to general population. Moreover, since Sports Medicine Specialists is still scarcely distributed through out the nation, itis imperative to integrate Sports Medicine knowledge in Primary Healthcare services. On the other hand, MISS is focusing on one of the most common sports injury and musculoskeletal injury in the community, i.e. ankle sprain. Various aspects of ankle sprain, from epidemiology to the current update of its management will be discussed to improve the management of ankle sprain in the community. Thus we sincerely hope this event will bring significant impact in improving the quality of the medical / sports professionals services for all the audience while enjoying the refreshing ambience of Bali, the Paradise Island. Thank you for your participation and contribution in this event. Warm regards, Dr. Rika Haryono, Sp.K.O., Subsp. ALK (K)